An update of the Italian Stroke Organization–Stroke Prevention Awareness Diffusion Group guidelines on carotid endarterectomy and stenting: A personalized medicine approach. Issue 5 (July 2017) - Lanza, Gaetano; Setacci, Carlo; Ricci, Stefano; Castelli, Patrizio; Cremonesi, Alberto; Lanza, Jessica; Novali, Claudio; Pratesi, Carlo; Santalucia, Paola; Speziale, Francesco; Zaninelli, Augusto; Gensini, Gian Franco
Although proof-based medicine has generated much valid evidence for the drawing up of guidelines and recommendations for best clinical practice in symptomatic and asymptomatic carotid stenosis, whether and when it is better to employ endarterectomy or stenting as the intervention of choice still remain matters of debate. Moreover, guidelines have been targeted up to now to the 'representative' patient, as resulting from the statistical analyses of the studies conducted on the safety and efficacy of both interventions as well as on medical therapy alone. The Italian Stroke Organization (ISO) and Stroke Prevention and Awareness Diffusion (SPREAD) group has thus decided to update its statements for an 8th edition. To this end, a multidisciplinary team of authors representing Italian scientific societies in the neurology, neuroradiology, vascular and endovascular surgery, interventional cardiology, and general medicine fields re-examined the literature available on stroke. Analyses and considerations on patient subgroups have allowed to model the risks/benefits of endarterectomy and stenting in the individual. Accordingly, the guideline's original methodology has been revised to follow the new SIGN (Scottish Intercollegiate Guideline Network) Grade-like approach, integrating it with new considerations on Precision, or Personalized Medicine. Therefore, this guideline offers recommendations on precision medicine for the single patient, and can be followed in addition to the more standard guidelines.